THE EFFECT OF IMPLEMENTING THE CONTEXTUAL TEACHING LEARNING (CTL) MODEL ASSISTED BY POP-UP BOOK MEDIA ON THE SOCIO-CULTURAL SKILLS OF ELEMENTARY SCHOOL STUDENTS - Nina Marlina; Sofyan Iskandar; Tiara Yogiarni (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Learning in elementary school is still often focused on cognitive aspects with a teacher-centered process and rarely connects the material to students' real-life context, so students' social and cultural skills tend to not develop optimally. This study aims to determine the effect of the Contextual Teaching and Learning (CTL) model assisted by Pop-Up Book media on elementary students’ socio-cultural skills and compare its effectiveness with the Cooperative Learning model. Using a quasi-experimental design with a Non-Equivalent Control Group Design, the research population comprised all fourth-grade students at SDN Karang Asih 08, Bekasi Regency. Purposive sampling selected 30 students for the experimental class (CTL with Pop-Up Books) and 28 for the control class (Cooperative Learning with PowerPoint). Data were collected via an 8-question essay test measuring four socio-cultural skill indicators based on the Ministry of Education and Culture (2020). Descriptive analysis showed the experimental class's mean posttest score (86.47) outperformed the control class (76.89). Simple linear regression yielded an R-Square of 0.299, indicating a significant 29.9% contribution of the CTL model with Pop-Up Books to skill improvement. Furthermore, the N-Gain Score analysis revealed the experimental class achieved 76.26% (effective category), whereas the control class only reached 55.50% (fairly effective category). In conclusion, implementing the CTL model assisted by Pop-Up Book media significantly affects and proves more effective in improving elementary students’ socio-cultural skills than the Cooperative Learning model.